\(A=\frac{x^2+2x+1-x-1+1}{\left(x+1\right)^2}=\frac{\left(x+1\right)^2}{\left(x+1\right)^2}-\frac{\left(x+1\right)}{\left(x+1\right)^2}+\frac{1}{\left(x+1\right)^2}\)
\(A=1-\frac{1}{x+1}+\left(\frac{1}{x+1}\right)^2\)
Đặt B=\(\frac{1}{x+1}\). ta có:
\(A=B^2-B+1=B^2-\frac{2B.1}{2}+\frac{1}{4}+\frac{3}{4}=\left(B-\frac{1}{2}\right)^2+\frac{3}{4}\ge\frac{3}{4}\)
dấu = xảy ra khi \(B-\frac{1}{2}=0\)
\(\Rightarrow B=\frac{1}{2}\). Vậy Min A=\(\frac{3}{4}\Leftrightarrow x=\frac{1}{2}\)
eei, sorry :>
\(B=\frac{1}{x+1}=\frac{1}{2}\Rightarrow x+1=2\Rightarrow x=1\)
=.=" sorry bn nha, t làm lộn